When to Scaffold Motivational Self-Regulation Strategies for High School Students' Science Text Comprehension - Michalsky, Tova (Frontiers in Psychology, 2021)
Motivation plays an important role in science students’ reading comprehension by regulating students’ engagement with the text and exercises and students’ perseverance of effort despite obstacles until successful completion. This 14-week quasi-experiment investigates the optimal timing for implementation of metamotivational scaffolding for self-regulation of scientific text comprehension. The “IMPROVE” metamotivational self-regulatory model (Introducing new concepts, Metamotivation questioning, Practicing, Reviewing and reducing difficulties, Obtaining mastery, Verification, and Enrichment) was embedded at three different phases of secondary students' engagement with scientific texts and exercises (before, during, or after) to examine effects of timing on groups’ science literacy and motivational regulation. Israeli 10th graders (N = 202) in eight science classrooms received the same scientific texts and reading comprehension exercises, in four groups. Three treatment groups received metamotivational scaffolding before (n=52), during (n=50), or after text engagement (n=54), respectively. The control group (n=46) received standard instructional methods with no metamotivational scaffolding. Pretests and posttests assessed science literacy, domain-specific microbiology knowledge, and metamotivation regulation. Intergroup differences were nonsignificant at pretest but significant at posttest. The “before” group significantly outperformed all other groups. The “after” group significantly outperformed the “during” group, and the control group scored lowest. Outcomes suggest that an important means for promoting students’ science literacy and effortful perseverance with challenging science tasks is to deliver metamotivational scaffolding, especially at the reflection-before-action stage for looking ahead, and also at the reflection-on-action stage for looking back. More theoretical and practical implications of this preliminary study are discussed to meet the growing challenges in science teaching schoolwork.